Effect of citric acid and glutamic acid on physiological traits and quotients The bean plant, Vicia faba L. (Journal of the College of Basic Education, 2022)
A field experiment was conducted in the Botanical Garden of the Department of Life Sciences at the College of Education for Pure Sciences/Ibn Al-Haytham, University of Baghdad, during the growing season (2014-2015) in order to study the effect of citric acid at two concentrations of 10 and 20 mg. L-1 and glutamic acid at two concentrations of 50 and 100 mg. L-1 on the growth and yield of the bean plant Vicia faba L..The results showed a significant increase in most phenotypic and physiological traits such as plant height, number of leaves, plant dry weight, chlorophyll content of leaves, number of flowers, absolute growth rate, crop growth rate, pod length and dry weight, number of pods and seed dry weight compared to control plants.